Fontan-associated liver disease: Diagnosis, surveillance, and management - de Lange, Charlotte; Möller, Thomas; Hebelka, Hanna (Frontiers in Pediatrics, 2023)
The Fontan operation is a lifesaving procedure for patients with functional single-ventricle congenital heart disease, where hypoplastic left heart syndrome is the most frequent anomaly. Hemodynamic changes following Fontan circulation creation are now increasingly recognized to cause multiorgan affection, where the development of a chronic liver disease, Fontan-associated liver disease (FALD), is one of the most important morbidities. Virtually, all patients with a Fontan circulation develop liver congestion, resulting in fibrosis and cirrhosis, and most patients experience childhood onset. FALD is a distinctive type of congestive hepatopathy, and its pathogenesis is thought to be a multifactorial process driven by increased nonpulsatile central venous pressure and decreased cardiac output, both of which are inherent in the Fontan circulation. In the advanced stage of liver injury, complications of portal hypertension often occur, and there is a risk of developing secondary liver cancer, reported at young age. However, FALD develops with few clinical symptoms, a surprisingly variable degree of severity in liver disease, and with little relation to poor cardiac function. The disease mechanisms and modifying factors of its development are still not fully understood. As one of the more important noncardiac complications of the Fontan circulation, FALD needs to be diagnosed in a timely manner with a structured monitoring scheme of disease development, early detection of malignancy, and determination of the optimal time point for transplantation. There is also a clear need for consensus on the best surveillance strategy for FALD. In this regard, imaging plays an important role together with clinical scoring systems, biochemical workups, and histology. Patients operated on with a Fontan circulation are generally followed up in cardiology units. Ultimately, the resulting multiorgan affection requires a multidisciplinary team of healthcare personnel to address the different organ complications. This article discusses the current concepts, diagnosis, and management of FALD, with special emphasis on the role of different imaging techniques in the diagnosis and monitoring of disease progression, as well as current recommendations for liver disease surveillance.